If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17w + 23 = -4 + -8w Reorder the terms: 23 + -17w = -4 + -8w Solving 23 + -17w = -4 + -8w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '8w' to each side of the equation. 23 + -17w + 8w = -4 + -8w + 8w Combine like terms: -17w + 8w = -9w 23 + -9w = -4 + -8w + 8w Combine like terms: -8w + 8w = 0 23 + -9w = -4 + 0 23 + -9w = -4 Add '-23' to each side of the equation. 23 + -23 + -9w = -4 + -23 Combine like terms: 23 + -23 = 0 0 + -9w = -4 + -23 -9w = -4 + -23 Combine like terms: -4 + -23 = -27 -9w = -27 Divide each side by '-9'. w = 3 Simplifying w = 3
| Y^2+6y=4 | | 2x-2y/3=6 | | 4a(x+3)=4ax+12a | | 4x^3+15x^2-12x+2=0 | | 5(3x-4)+2=7(2x-3) | | tan^2(x)=1/343 | | 40*1000= | | 15x^2-16x+6=0 | | x=(y-3)-9*7 | | 3a+2=16a+48 | | 13x+1=8x+26 | | x/100=0.65 | | 2w-3w-14=0 | | x^2+2=48 | | 2w-3w=0 | | 2q-10=q-4 | | x^2-12x-57=0 | | 0=18x+10 | | y=18x+10 | | 5y-3x-4=0 | | x^2+10x+25-2x^2+2x+32=0 | | z=(x-a)/b | | 8x=-2y+8 | | -8x+15=0 | | 4a^2-4b^2+16bc-16c^2=0 | | X+3x^2=52 | | 4ln(x)=ln(81) | | 9x(-5*42)=0x | | 3y-6x+24=0 | | 9x(-5*42)=3x | | 2x[12+9]= | | -4(b-1)+2b=3(2b-1) |